Respuesta :
Answer:
5x^2+1
Step-by-step explanation:
2x^2 and 3x^2 are like terms so just add them which gives 5x^2.
2 and -1 are like terms so combine them to make 1.
Answer:
5x²-1
Step-by-step explanation:
We are given the expression:
[tex]2x^2+2 + 3x^2- 1[/tex]
and asked to simplify.
To simplify this expression, we must combine like terms.
2x²⇒ this has a variable, x²
2⇒ no variable
3x²⇒this has a variable, x²
-1⇒ no variable
Group the like terms.
[tex](2x^2 + 3x^2)+(- 1+2)[/tex]
Add 2x² and 3x². Add the coefficients and add an x² on the end.
[tex](2+3)x^2+(-1+2)[/tex]
[tex](5)x^2+(-1+2)[/tex]
[tex]5x^2+(-1+2)[/tex]
Combine -1 and 2.
[tex]5x^2+(-1)[/tex]
[tex]5x^2-1[/tex]
The expression 2x²+2+3x²-1 simplified is 5x²-1